2015
DOI: 10.5009/gnl14338
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Inflammatory Bowel Disease in Korea: Comparison with EUROKIDS Data

Abstract: Background/AimsPediatric inflammatory bowel disease (IBD) has been increasing worldwide. The characteristics of pediatric-onset IBD have mainly been reported in Western countries. We investigated the clinical characteristics of pediatric IBD in Korea and compared these with the data from the 5-year European multicenter study of children with new-onset IBD (EUROKIDS registry).MethodsChildren who were diagnosed with IBD between July 1987 and January 2012 were investigated at five Korean university hospitals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
7
23
1
Order By: Relevance
“…Our study revealed that pediatric onset cases accounted for 12.7% of all CD cases and elderly onset cases accounted for 2.5%, which was similar to the results of these Western studies. The female predominance in the elderly onset group and a higher frequency of perianal fistula in the pediatric onset group are consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that pediatric onset cases accounted for 12.7% of all CD cases and elderly onset cases accounted for 2.5%, which was similar to the results of these Western studies. The female predominance in the elderly onset group and a higher frequency of perianal fistula in the pediatric onset group are consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, perianal disease was recorded in 21.6% of our cohort, which represents a considerably higher percentage than that found in Western data (8–10%) . Our results are similar to those of a recent Korean study, which report a high rate of perianal disease in 33.3% (10/30) of CD patients . As suggested by the authors, the predominance of perianal disease could potentially be a distinguishable difference between Asian and Western patients with pediatric CD .…”
Section: Discussionsupporting
confidence: 86%
“…The median age at initial diagnosis of IBD in our population was 10.47 years, which was notably younger than those reported in other countries; in Europe and North America, the median age at diagnosis was approximately 12–13 years, whereas in Korea, it was 15 years. A worrisome finding is that almost one‐fifth of our cohort was under 6‐years‐old when they presented with very early‐onset IBD, which is a considerably higher proportion than that reported in the West, where 7–11% of the cohort presented with very early‐onset IBD .…”
Section: Discussioncontrasting
confidence: 65%
“…The introduction of anti-tumor necrosis factor (anti-TNF) agents has greatly improved the treatment outcomes for IBDs, enabling higher rates of clinical and endoscopic remission in patients who are refractory to conventional therapies such as corticosteroids and thiopurines 1,2. Despite the proven therapeutic efficacy of anti-TNF agents, treatment failures to those sometimes occur in the form of primary nonresponse or secondary loss of response (LOR).…”
mentioning
confidence: 99%